Instructions matter: a comparison of baseline conditions for cognitive emotion regulation paradigms - Diers, Kersten; Weber, Fanny; Brocke, Burkhard; Strobel, Alexander; Schönfeld, Sabine (Frontiers in Psychology, 2014)
The choice of a meaningful baseline condition is a crucial issue for each experimental design. In the case of cognitive emotion regulation, it is common to either let participants passively view emotional stimuli without any further specific instructions or to instruct them to actively attend to and permit any arising emotions, and to contrast one of these baseline conditions with a regulation condition. While the “view” strategy can be assumed to allow for a more spontaneous emotional response, the “permit” strategy may result in a more pronounced affective and cognitive response. As these conceptual differences may be associated with differences both in subjective emotional experience and neural activation, we compared these two common control conditions within a single functional magnetic resonance imaging (fMRI) experiment, during which participants were instructed to either passively view a set of unpleasant and neutral pictures or to actively permit any emotions arising in response to the unpleasant pictures. Trial-by-trial ratings confirmed that participants perceived the unpleasant pictures as more arousing than the neutral pictures, but also indicated higher subjective arousal during the “permit negative” as compared to the “view negative” and “view neutral” conditions. While both the “permit negative” and “view negative” conditions led to increased activation of the bilateral amygdala when contrasted with the passive viewing of neutral pictures, activation in the left amygdala was increased in response to the “permit” instruction as compared to the “view” instruction for unpleasant pictures. The increase in amygdala activation in both the “permit” and “view” conditions renders both strategies as suitable baseline conditions for studies of cognitive emotion regulation. Conceptual and activation differences, however, indicate that these two variants are not exchangeable and should be chosen depending on the experimental context.